Competition for small firm banking business: Bank actions versus market structure - Scott, Jonathan A.; Dunkelberg, William C. (Journal of Banking & Finance, 2010)
This paper addresses two questions related to the ongoing consolidation of the US banking industry and its effect on small firm financing. First, are conventional measures of market structure (e.g. geographic market size and deposit concentration) related to bank competition for small firm financial business? Second, does an increase in bank competition produce an improvement in bank services irrespective of market structure? To answer these questions we use a survey of small firm owners that asks them to report on changes in bank competition for their business. Our findings show that reports of increased competition by small firm owners are negatively related to the level of and change in deposit concentration. In addition, we find a significant positive association between changes in bank competition reported by small firms and their reports of changes in banking outcomes (e.g. service quality) that is independent of deposit concentration, firm risk, and credit usage.